The impact of telemedicine on health care management - Nerlich, Michael (Studies in health technology and informatics, 1999)
Title page -- Contents -- Introduction -- Editorial -- Acknowledgements -- The Impact of Telemedicine on Health Care Management -- The G8-Global Health Care Applications Project (GHAP) and its Role for the Development of National Telemedicine Activities -- International Concerted Actionon Collaboration in Telemedicine: G8 sub-project 4 -- Background Information -- Concepts and Experiences -- Towards a Methodology for Developing and Implementing Best Practices in Telehealth and Telemedicine -- Theory of Use behind Telehealth Applications -- The Value of an Evaluation Framework for Telehealth Initiatives -- Assessing the Impact of Telemedicine on Health Care Management -- A Review of Japanese Telemedicine Research and Global Co-Operation -- Telehealth in British Columbia: From Design to Delivery -- Legal Solutions for Telemedicine -- The SIREN Legal Workshops: List of Urgent Legal Actions for Telemedicine -- Health Care Professionals Protocol for Secure Online Transmission of Patient Data -- Results of European Projects Enabling Secure Regional, National and International Health Care Networks -- Telemedicine Applications For Clinical Practice -- Accident and Emergency -- NOAHA Mobile Emergency Care System -- MediLink: A Wearable Telemedicine System for Emergency and Mobile Applications -- Surgery -- Integration of Quality Programs by Telemedicine in Surgical Services -- Telemedicine in Neurosurgical Daily Practice -- Oncology -- Perfect DiViSy Technology for Video Network in Medicine (Moscow Information Network for Teleoncology) -- Cardiology -- A Controlled Pilot Study in the Use of Telemedicine in the Community on the Management of Heart Failure -- Telematic-Based Model of Early Diagnosis and Treatment of Acute Coronary Syndromes -- Endocrinology -- Telemedicine and Diabetes -- Ophthalmology
Keywords: Konferenzschrift -- 1998 -- Regensburg; Telemedizin